The Effects of Cost Leadership Strategy and Product Differentiation Strategy on the Performance of Firms - Valipour, Hashem; Birjandi, Hamid; Honarbakhsh, Samira (Journal of Asian Business Strategy, 2012)
This study empirically investigates the effects of business strategies on the relationship between financial leverage and the performance of firms. The research data is collected from 45 firms in the Tehran Security Exchange (TSE) during 2003-2010.The statistical technique is used to examine the assumption of multiple regressions. To test the assumptions, firms were divided into 2 groups: firms with cost leadership strategy and firms with product differentiation strategy. The results indicated that in the firms with cost leadership strategy, there were positive relationships between leverage; cost leadership strategy and dividend payout with performance. The results also suggested that there were positive relationships between leverage and firm's size with performance in the firms with product differentiation strategy, but the relation between product differentiation strategy and dividend payout with performance was negative.